EROSITA study of the globular cluster 47 Tucanae - Saeedi, Sara; Liu, Teng; Knies, Jonathan; Sasaki, Manami; Becker, Werner; Bulbul, Esra; Dennerl, Konrad; Freyberg, Michael; Laktionov, Roman; Merloni, Andrea (Astronomy & Astrophysics, 2022)
Aims. We present the results of the analysis of five observations of the globular clutser 47 Tucanae (47 Tuc) with the extended Roentgen Survey with an Imaging Telescope Array (eROSITA) on board the Spektrum-Roentgen-Gamma (Spektr-RG, SRG). We study the X-ray population in the field of one of the most massive globular clusters in our Milky Way. We focused on the classification of point-like sources in the field of 47 Tuc. The unresolved dense core of 47 Tuc (1.7 radius) and also sources that show extended emission are excluded from this study. Methods. We applied different methods of X-ray spectral and timing analysis together with multi-wavelength studies to classify the X-rays sources in the field of 47 Tuc. Results. We detected 888 point-like sources in the energy range of 0.2a-5.0 keV. We identified 126 background active galactic nuclei and 25 foreground stars. One of the foreground stars is classified as a variable M dwarf. We also classified 14 X-ray sources as members of 47 Tuc, including one symbiotic star, two quiescent low-mass X-ray binaries, and four cataclysmic variables. There are also five X-ray sources that can either be a cataclysmic variable or a contact binary, and also one X-ray source can be an active binary (type RS CVn). We identified one X-ray binary that belongs to the Small Magellanic Cloud. Moreover, we calculated the X-ray luminosity function of 47 Tuc. No significant population that seems to belong to the globular cluster is observed in the energy range of 0.5-2.0 keV using eROSITA observations.
CRIS-Team Scopus Importer:2022-06-10
Keywords: Binaries: Symbiotic; Globular clusters: General; Novae; cataclysmic variables; X-rays: Binaries